Computational thinking and problem-solving methodology: Possible approaches in the context of mathematics teaching and learning - Boccardo , Mateus Eduardo; Meneghetti , Renata Cristina Geromel (Seven Editora, 2023)
Despite being lacking in number of articles, dissertations and theses produced, research relating Computational Thinking and Mathematics are standing out in the country and studies on this relationship are gaining more and more space. In this direction, this work aims to discuss about some theoretical approximations between computational thinking and the methodology of problem solving focused on the process of teaching and learning mathematics. To this end, following a qualitative research approach, at first, theoretical aspects of Computational Thinking and Problem Solving methodology will be presented. Subsequently, it will be discussed about some possible relationships between Computational Thinking and the methodology of Problem Solving, with regard to the process of teaching and learning Mathematics. As a result, it was possible to observe that Computational Thinking and Problem Solving Methodology have their pillars in the constructivist trend of education and conceive the problem as a starting point and essential for the teaching and learning process, in addition to valuing creativity, problem decomposition, abstraction and pattern recognition, important characteristics to improve the learning of Mathematics. DOI:https://doi.org/10.56238/ptoketheeducati-037